Reconstruction of Uncertain Historical Evolution of the Polysyllablization of Chinese Lexis. (13th July 2014) - Qiu, Bing; Li, Jie
Abstract : Polysyllablization, closely related to phonetics, semantics, and syntactics, is one of the fundamental trends in the development of Chinese lexis. However, with lots of uncertainties in the historical evolution of Chinese language, the quantitative modeling and reconstruction of polysyllablization remain open questions. Based on the Comprehensive Dictionary of Chinese Words, a mapping from the words to their time of occurrence is built. With the inverse mapping on random samples, the newly produced words with different numbers of syllables in different time periods are obtained. Finally the total quadratic variation minimization model is adopted to estimate the trend of polysyllablization. As a novel exploration in the computational linguistics, the results agree with the stage division of historical Chinese and answer some difficult questions related to polysyllablization in a quantitative manner.